Breath Dhikr Therapy Training for NU Women in Sedayu Village, Gemuh District, Kendal Regency - Aulia Ainis Lisa; Aulia Rizki Rahmawati (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Physical and mental health are two essential aspects that are interconnected in an individual's life. In Islamic teachings, maintaining a balance between the two is highly emphasized to achieve happiness in this world and the hereafter. Dhikr, the act of remembering Allah SWT, not only brings inner peace but also has the potential to improve mental and physical health when combined with proper breathing techniques. This study was conducted in Sedayu Village, Gemuh District, Kendal Regency, where many Muslimat members experience stress and physical fatigue due to their demanding routines. A dhikr-breathing therapy training was introduced as an integrative solution, combining spiritual practices with breathing techniques to enhance participants' well-being. The study employed a qualitative approach, involving 30 participants in the dhikr-breathing training. The results showed that the training effectively reduced stress levels and improved both physical and mental well-being. Although challenges in maintaining consistency were observed, most participants expressed a willingness to continue the practice. Therefore, dhikr-breathing has the potential for sustainable implementation as a practical method for improving the quality of life among Muslimat members.